Hemodynamic Dysfunctions in COVID-19 Patients (Research, Society and Development, 2021)
Coronavirus disease 2019 (COVID-19) is a respiratory viral infection caused by the novel coronavirus (SARS-CoV-2). Thus, it objected to comprehend the pathophysiology of COVID-19, as well as its clinical repercussions on hemodynamic alterations. This is an integrative literature review, such a method is able to select and include experimental and non-experimental studies, qualitative in nature, descriptive and exploratory in character. Initially, it started from the guiding question: "What hemodynamic dysfunctions can the positive COVID-19 patient develop?" The study was conducted by searching the database: PUBMED, using the descriptors: "coagulopathy" and "COVID-19", combined by the Boolean operator AND. As inclusion criteria, the filters of one-year version, full text, clinical trial, meta-analysis, and randomized controlled trial were chosen. Coagulopathy and thromboembolic events are manifestations of COVID-19 and are designated as poor prognostic factors. The respiratory system is the main target of SARS-CoV-2, but other body systems may also be involved. Therefore, symptoms can range from respiratory distress to multiple organ failure. It is concluded that the presence of coagulopathy is a major source of mortality in COVID-19 positive patients. Also, coagulopathy is linked to the severity of the symptomatology of COVID-19, and that in more severe cases relatively increased levels of D-dimer, prothrombin time, and fibrinogen are present. In addition, no significant minimization in platelet levels was observed in severe cases of COVID-19.